Variation of biogenic nutrients in lake water under different levels of anthropogenic impact - Stankevičienė, Rasa; Survilė, Oksana; Kalibatienė, Diana (International Conference “Environmental Engineering”, 2026)
This article analyzes the water quality of three lakes under different anthropogenic influences. It examines seasonal changes in biogenic substance concentrations and pH, as well as the impact of environmental use on the ecological status of the lakes. A comparison of one year’s water testing data for Lakes Girbys, Dauniškis, and Lydekis (Utena County) shows that the highest concentrations of biogenic substances and the most pronounced risk of eutrophication are characteristic of lakes affected by intensive agricultural activity. The lake located in an urbanized area is characterized by greater fluctuations in biogenic substances. The lake located in a natural, wooded environment is characterized by stable water quality and the least anthropogenic impact. The results of the study show that the water quality of lakes is determined not only by their natural characteristics, but also by the intensity and nature of environmental use.
Keywords: anthropogenic impact; water quality; biogenic substance; lakes